Avautuva talous ja aluekehitys: Suhteellinen etu ja kasautumisvoimat tuotannon sijoittumisen ohjaajina suomessa - Mika Widgrén; Kari Alho; Markku Kotilainen; Nuutti Nikula; Ville Kaitila (The Research Institute of the Finnish Economy (ETLA), 2007)
– The study examines the developments in production structures in Finnish regions and the differences in regional income levels and the causes that affect them in an integrating global economy as well as the challenges facing regional policies. The increasing openness of the world economy, the increasing competition it causes and its effect on Finland's regions is the central task of this study. We combine the classical theory of international trade based on comparative advantage about the specialisation of countries with the approach of the new economic geography and agglomeration forces about the specialisation of regions inside countries. The study is a pioneer in Finland because similar analysis of regional production structures and specialisation has not been done before. We find that the so-called agglomeration forces drive the location of production in Finland. These regional agglomeration forces are the economic size of the region and closeness to markets (so-called market potential), distance between companies producing intermediate and final products, scale effects, and the educational level and R&D activities. Centralisation of production also requires that workforce is willing to relocate and that the productivity growth in core areas is faster than on average. Because labour mobility is such a central requirement for production agglomeration the study also examines migration within Finland in the past 50 years. For regional policies the conclusion of the study is that agglomeration forces should not be constrained if they lead to and are caused by faster productivity growth in core regions. In Finland there are significant differences in public sector services per capita in different regions so that regions with low wage and tax revenues have more public sector services in per capita terms than the core regions. This means that it is very hard to stop migration flows using the community tax equalisation scheme.
Keywords: R12; R15; R38; 330; regional economy; agglomeration forces; comparative advantage; new economic geography